Some results on cryptanalysis of SMS4 block cipher. (2nd July 2010) - Zhang, Wentao; Su, Bozhan; Wu, Wenling; Feng, Dengguo
SMS4 is a 128-bit block cipher used in the WAPI standard in wireless networks in China. The cipher has attracted much attention in the past several years. This paper consists of two parts. The first part is on the design of the linear diffusion layer L of SMS4. Some observations on L are present, which open out the design rationales of L and such class functions to a great extent. The second part is on the differential attack against SMS4. An effective 19-round differential characteristic is presented. Then, a simple differential attack on 23-round SMS4 is given, which is the best known attack on SMS4 so far.